FIRM VALUE, CAPITAL STRUCTURE, PROFITABILITY, FIRM CHARACTERISTIC AND DISPOSIBLE INCOME AS MODERATOR: AN EMPIRICAL INVESTIGATION OF RETAIL FIRMS IN INDONESIA - Mamay Komarudin; Naufal Affandi (Politeknik Negeri Bengkalis, 2019)
This study examined the effect of capital structure on firm value; firm characteristic on firm value with disposible income as moderator variable; the effect of profitability on firm value. The study was conducted in Indonesia Stock Exchange (IDX) with samples of retail firms listed on the IDX in 2014 to 2016 as many as 21 retail firms. The analysis methode used Moderated Regression Analysis (MRA), classical assumption test and t test. The results showed that the capital structure didn’t have a significant negative effect on firm value. Profitability had a significant positif effect on firm value. Firm characteristic didn’t have a significant negative effect on firm value with disposible income as a moderator. The conclusion of research indicated that capital structure and profitability had a significant effect on firm value while firm characteristic with disposible income as moderator didn’t have significant effect on firm value